Relationship of Phubbing to Self-Esteem in the Context of Perceived Phubbing Behavior of Parents - Weimann, Bogumiła; Cholewa, Malwina; Kleka, Paweł (Przegląd Psychologiczny, 2024)
Purpose: Phubbing is a phenomenon whereby a person looks at their mobile phone and uses it while talking to others, thereby avoiding interpersonal communication (Karadağ et al., 2015). The study aimed to investigate whether phubbing by parents correlates with phubbing by their adult children, whether phubbing by parents is associated with children's self-esteem (in adulthood) and whether children's self-esteem (in adulthood) is correlated with their level of phubbing. Method: 107 people from Poland participated in the study. The authors used the Rosenberg Self-Esteem Scale (SES), the Generic Scale of Phubbing (GSP), and self-report questions to verify the level of phubbing used by the subjects' parents. Results: The results showed a positive correlation (r = .37, p < .001) between parents' phubbing and children's phubbing, as well as between children's self-esteem and phubbing by parents (r = .37; p < .001) and between children's phubbing and their self-esteem (r = .46, p < .001). Conclusion: The study confirms the modelling role of parental phubbing for the intensity of children's phubbing, but at the same time, it does not show a negative role in children's self- esteem. Furthermore, the positive correlation between children's phubbing and self-esteem contradicts previous results. Children's phubbing partially mediates the relationship between parents' phubbing and their self-esteem, which requires further research to understand this mechanism more fully.